SCD and Associated Syndromes in the Young - Sinclair, Heather Q. (MD Conference Express, 2010)
Sudden cardiac death (SCD) is a leading cause of death in the United States (amounting to 1 death every 80 seconds, or 450,000 deaths annually), with >50% of these events having a genetic etiology [Behr ER et al. Eur Heart J 2008]. There are several syndromes that are associated with SCD in the young, including congenital long QT syndrome, hypertrophic cardiomyopathy, arrhythmic right ventricular dysplasia, Brugada syndrome, and cathecholamine polymorphic ventricular tachycardia. This article discusses ways to identify these high-risk syndromes and current clinical approaches to SCD prevention in the young.